PERJANJIAN PERDAGANGAN PREFERENSI INDONESIA-MOZAMBIK - Nurul Sakinah Arif; Arie Kusuma Paksi (Cakrawala Jurnal Penelitian Sosial, 2021)
The relationship between Indonesia and Mozambique has been established since 1991. From time to time, the bilateral relations between Indonesia and Mozambique have become stronger, marked by increased visits between government officials and businessmen of the two countries. Between the two countries, various Memorandum of Understanding (MoU) have been signed in various fields, especially in the trade sector. In line with the guidelines for Mozambique's largest exhibition, the 55th International Trade Fair – FACIM to be precise on 29 August 2019, the Indonesian Minister of Trade (Menteri Perdagangan), Enggartiasto Lukita and the Minister of Industry and Trade of Mozambique Ragendra Berta de Sousa signed the Indonesia-Mozambique Preferential Trade Agreement (IM-PTA).The launch of the IM-PTA negotiations was carried out in 2018 by the Indonesian Minister of Trade and the Minister of Industry and Trade of Mozambique as the first bilateral agreement between both country. This paper analyzes the reasons behind Indonesia's foreign policy in deciding to signed the IM-PTA. The author uses the concepts of National Interest to identify Indonesian foreign policy decision-making. A qualitative descriptive approach is used to reveal information and data about the phenomena. The author reviews data from books, journals, papers, government data, and credible articles on the internet. After collecting data, the author analyze and summarize the information related to the topic. Research shows that Indonesia's foreign policy to signed the IM-PTA is based on the national interest of Indonesia to obtain a trade surplus. This agreement also opens the way for Indonesia to enter the market in the African continent as a stepping stone to enter the African continent.